Synthesis, Spectral Characterization and In-Vitro Biological Evaluation of Novel 5-Methoxy / 5-Ethoxy Benzimidazole-2-Thiol Derivatives as Antibacterial, Antifungal, Anti-tubercular and Antioxidant Agents - tiwari, Dheeraj Kumar; S, Rajasekaran (Journal of Neonatal Surgery, 2025)
The present study focuses on the design, synthesis, spectral characterization, and comprehensive in-vitro biological evaluation of a novel series of 2-(5-substituted-1H-benzimidazol-2-ylthio)-N-arylacetamide derivatives (SS1–SS21), developed to explore their antibacterial, antifungal, antitubercular, and antioxidant potential. The synthetic strategy involved S-alkylation of 5-methoxy, 5-ethoxy, and 5-chloro benzimidazole-2-thiols with appropriately substituted N-(chloroacetyl) aryl amines, affording the target compounds in good yields. Structural elucidation was achieved through FT-IR, ¹H-NMR, mass spectrometry, melting point analysis, and TLC profiling, all confirming the successful formation of the designed thioether-linked N-aryl acetamides. Antibacterial assays performed against Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, and Bacillus subtilis revealed that several derivatives, particularly nitro- and chloro-substituted analogues, exhibited MIC values comparable to or better than ampicillin. Antifungal evaluation against Candida albicans, Aspergillus niger, Epidermophyton floccosum, Trichophyton rubrum, and wild Penicillium spp. demonstrated that methoxy- and ethoxy-substituted derivatives displayed strong fungicidal activity, in several cases approaching or surpassing Griseofulvin and nearing Nystatin efficacy. Antitubercular screening against Mycobacterium tuberculosis H37Rv identified SS5 and SS15 as moderately active, which correlated well with molecular docking studies showing favourable binding energies and key interactions with cyclopropane-fatty-acyl-phospholipid synthase enzymes (PDB: 1KPG, 1KPI). Antioxidant assessment using the DPPH assay revealed potent radical-scavenging properties for electron-donating methoxy and ethoxy derivatives, especially SS9 and SS10. Structure–activity relationship analysis indicated that electron-withdrawing substituents enhanced antibacterial potency, while electron-donating groups favored antifungal and antioxidant effects. Overall, the study presents benzimidazole-2-thiol-based N-aryl acetamides as promising multifunctional agents with significant antimicrobial and antioxidant potential, offering valuable scaffolds for future optimization and drug development..